Integrating and Sustaining Creativity in the Language Arts Classroom - Batanian, Morgan (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
This essay examines the significance of integrating creativity in the English Language Arts (ELA) classroom by exploring the beneficial effects that nurturing creativity has on students. Based on theories and research on creativity and the learning experience, it proposes that students have an opportunity to enhance their personal and academic skills if teachers properly integrate creative activities into the classroom. Creative opportunities need to be encouraged and integrated regularly within the ELA classroom, as it is important to students’ overall success in achieving higher-order levels of thinking. However, for students to both engage in creative activities and also believe in their creative abilities, their teachers must actively foster their belief in their own abilities and offer them opportunities to be creative.